Optimizing Care: The Impact of Medical Devices on Healthcare Staff Performance and Well-Being – A Comprehensive Review - Al mansour, Mohammed Hadi; Alyami, Nasser Shedad Saleh; Al Garaawi , Abdullah Saleh Ali; Al Busus , Mana Yahya Mishaa; Lasloum, Mesfer Jaber Salem; Al Doghman, Hussein Eidah Saeed; Al Monajjam, Salim Heshaan; Zabadeen , Mohammed Saleh Mohammed; Al alhareth, Abdallah Mohamed; Ali Alsogoor , Fares Mohd (Journal of Ecohumanism, 2024)
Medical devices have become integral to modern healthcare, transforming clinical workflows and influencing the performance and well-being of healthcare staff. This review examines the dual impacts of medical devices on medical personnel, including improvements in efficiency, accuracy, and patient care, alongside challenges such as increased workload, stress, and ergonomic concerns. By synthesizing recent literature, the study identifies key trends, explores implications for clinical practice, and proposes strategies to optimize the integration of medical devices into healthcare environments. Emphasis is placed on enhancing device usability, supporting staff adaptation, and ensuring holistic well-being to foster sustainable improvements in healthcare delivery.